2017
DOI: 10.3389/fimmu.2017.01596
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) Promotes Resolution of Neutrophilic Inflammation in a Model of Antigen-Induced Arthritis in Mice

Abstract: Defective resolution of inflammation may be crucial for the initiation and development of chronic inflammatory diseases, such as arthritis. Therefore, it has been suggested that therapeutic strategies based on molecules that facilitate inflammation resolution present great potential for the treatment of chronic inflammatory diseases. In this study, we investigated the effects and role of angiotensin-(1-7) [Ang-(1-7)] in driving resolution of neutrophilic inflammation in a model of arthritis. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 51 publications
6
56
0
Order By: Relevance
“…Here, we showed that the preventive treatment with Ang‐(1‐7) caused reduction in the number of neutrophils and mononuclear cells in the lungs of mice given BLM. The ability of Ang‐(1‐7) to prevent neutrophil influx could be due to a direct effect on neutrophil migration in vivo or the ability of this compound to induce neutrophil apoptosis and resolution . The exact mechanism by which Ang‐(1‐7) causes inhibition of neutrophil migration was not investigated here, but there was a clear reduction in neutrophil numbers and an increase in number of apoptotic cells in animals given preventive Ang‐(1‐7) treatment.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Here, we showed that the preventive treatment with Ang‐(1‐7) caused reduction in the number of neutrophils and mononuclear cells in the lungs of mice given BLM. The ability of Ang‐(1‐7) to prevent neutrophil influx could be due to a direct effect on neutrophil migration in vivo or the ability of this compound to induce neutrophil apoptosis and resolution . The exact mechanism by which Ang‐(1‐7) causes inhibition of neutrophil migration was not investigated here, but there was a clear reduction in neutrophil numbers and an increase in number of apoptotic cells in animals given preventive Ang‐(1‐7) treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Ang‐(1‐7) has been shown to have anti‐inflammatory and proresolutive effects in murine models of arthritis and asthma . Due to this, we wondered if the oral treatment with Ang‐(1‐7) would decrease inflammation and collagen deposition in a model of pulmonary fibrosis induced by BLM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations